Electromyographic Response of Global Abdominal Stabilizers in Response to Stable- and Unstable-Base Isometric Exercise. Issue 6 (June 2015) - Atkins, Stephen J.; Bentley, Ian; Brooks, Darrell; Burrows, Mark P.; Hurst, Howard T.; Sinclair, Jonathan K.
Abstract : Abstract: Atkins, SJ, Bentley, I, Brooks, D, Burrows, MP, Hurst, HT, and Sinclair, JK. Electromyographic response of global abdominal stabilizers in response to stable- and unstable-base isometric exercise. J Strength Cond Res 29(6): 1609–1615, 2015—Core stability training traditionally uses stable-base techniques. Less is known as to the use of unstable-base techniques, such as suspension training, to activate core musculature. This study sought to assess the neuromuscular activation of global core stabilizers when using suspension training techniques, compared with more traditional forms of isometric exercise. Eighteen elite level, male youth swimmers (age, 15.5 ± 2.3 years; stature, 163.3 ± 12.7 cm; body mass, 62.2 ± 11.9 kg) participated in this study. Surface electromyography (sEMG) was used to determine the rate of muscle contraction in postural musculature, associated with core stability and torso bracing (rectus abdominus [RA], external obliques [EO], erector spinae [ES]). A maximal voluntary contraction test was used to determine peak amplitude for all muscles. Static bracing of the core was achieved using a modified "plank" position, with and without a Swiss ball, and held for 30 seconds. A mechanically similar "plank" was then held using suspension straps. Analysis of sEMG revealed that suspension produced higher peak amplitude in the RA than using a prone or Swiss ball "plank" ( p = 0.04). This difference was not replicated in either the EO or ES musculature. We conclude that suspension training noticeably improves engagement of anterior core musculature when compared with both lateral and posterior muscles. Further research is required to determine how best to activate both posterior and lateral musculature when using all forms of core stability training.